Critical review of clinical data and expert-based recommendations for the use of bosutinib in the treatment of chronic myeloid leukemia - García-Gutiérrez, Valentín; Gómez-Casares, María Teresa; Xicoy, Blanca; Casado-Montero, Felipe; Orti, Guillermo; Giraldo, Pilar; Hernández-Boluda, Juan Carlos (Frontiers in Oncology, 2024)
Chronic myeloid leukemia (CML), characterized by the presence of the BCR::ABL1 fusion gene, has undergone a transformative shift with the introduction of tyrosine kinase inhibitors (TKIs). The current availability of six different TKIs (imatinib, dasatinib, nilotinib, bosutinib, ponatinib, and asciminib) in clinical practice makes it important to know their efficacy and toxicity profile for treatment optimization. This review examines the latest insights regarding the use of bosutinib in CML treatment. Clinical trials have demonstrated the effectiveness of bosutinib, positioning it as a first-line treatment that can induce sustained molecular responses. Importantly, it can also be effective in patients who have experienced treatment failure or intolerance with prior TKIs, revealing the potential of bosutinib also in second-and later-line settings. Even in the advanced phase of CML, bosutinib has demonstrated its capacity to achieve molecular responses, expanding its usefulness. Real-world evidence studies echo these findings, emphasizing bosutinib's effectiveness in achieving deep molecular responses, maintaining remissions, and serving as an alternative for patients intolerant or resistant to other TKIs as a second-line therapy. Notably, one of the greatest strengths of bosutinib is its favorable safety profile, in particular the low incidence of vascular complications with its use, which is undoubtedly a comparative advantage over other TKIs. In summary, the latest research highlights the versatility of bosutinib in CML treatment and underscores its pivotal role in optimizing patient management in challenging cases. Continuing research and investigation will further establish bosutinib's place in the evolving landscape of CML therapy, offering an alternative for CML patients across different treatment stages.